2006
DOI: 10.1016/j.alcohol.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic daily ethanol and withdrawal: 6. Effects on rat sympathoadrenal activity during “abstinence”

Abstract: We have reported that repetitive daily ethanol consumption increased anxiety-like behavior in rats 4 weeks after ethanol consumption had ceased, consistent with the persistently increased anxiety exhibited by abstinent alcoholics. Increased anxiety is associated with sym-pathoadrenal activation, so we have now also investigated ethanol-induced persistent changes in basal and stress-induced plasma epinephrine (E) and norepinephrine (NE) levels. Male Sprague-Dawley rats received liquid diet containing ethanol ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Although sympathetic activation is increased during alcohol deprivation in rats and humans (Ehrenreich et al, 1997;Patkar et al, 2004;Rasmussen et al, 2006) and excessive brain and peripheral noradrenergic activation are associated with increased anxiety (Sullivan et al, 1999), it remains to be determined how acutely blocking noradrenergic signaling (including potential interactions between noradrenergic and CRF signaling) at the time of stress suppresses anxiety-like behavior during a subsequent alcohol deprivation 7 days later. It has been demonstrated that administrations of corticosterone instead of stress do not decrease subsequent alcohol deprivation-induced anxiety in this model (Breese et al, 2004), so it is unlikely that prazosin effects on corticosterone secretion play an important mediating role.…”
Section: Discussionmentioning
confidence: 99%
“…Although sympathetic activation is increased during alcohol deprivation in rats and humans (Ehrenreich et al, 1997;Patkar et al, 2004;Rasmussen et al, 2006) and excessive brain and peripheral noradrenergic activation are associated with increased anxiety (Sullivan et al, 1999), it remains to be determined how acutely blocking noradrenergic signaling (including potential interactions between noradrenergic and CRF signaling) at the time of stress suppresses anxiety-like behavior during a subsequent alcohol deprivation 7 days later. It has been demonstrated that administrations of corticosterone instead of stress do not decrease subsequent alcohol deprivation-induced anxiety in this model (Breese et al, 2004), so it is unlikely that prazosin effects on corticosterone secretion play an important mediating role.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in HPA axis responses have been observed during active drinking, acute withdrawal, and 4 weeks postwithdrawal from alcohol (Wand and Dobs, 1991;Adinoff et al, 1991Adinoff et al, , 2005Koob et al, 2004). Furthermore, autonomic dysregulation has been noted during acute alcohol withdrawal, and altered cardiovascular and noradrenergic responsivity has been seen during the protracted alcohol abstinence period (Krystal et al, 1996;Bernardy et al, 2003;Rasmussen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using animal models of drug self-administration and reinstatement, preclinical studies have shown CRF antagonists and α-2-adrenergic agonists to be efficacious in reducing stress-related drug seeking in addicted laboratory animals (see Shaham et al 2003;Weiss 2005 for review). Similarly, α1-adrenergic antagonists such as Prazosin have been found to decrease alcohol withdrawal symptoms, alcohol consumption and stress-induced relapse in animal models (Gilpin et al 2009;Rasmussen et al 2006;Walker et al 2008) and in a pilot clinical study of alcoholics (Simpson et al 2009). …”
Section: Related Relapsementioning
confidence: 99%